Santri and the Digital Divide: (The Upheaval of Pesantren Over Technological Developments in Cultural Lag Perspective) - Aprilia, Try Heni; Sufirmansyah, Sufirmansyah (Universitas Nahdlatul Ulama Blitar, 2025)
This paper focuses on the challenges and responses of pesantren in the information age. It starts from the assumption of pesantren as a subculture that filters out various external elements that seem more dominant to ensure the integrity of Islam. This character is the reason why pesantren can exist for a very long time. The purpose of this study was to determine the extent of the digital divide among santri at Salafiyah Islamic Boarding School. The method used is a mixed method with a Sequential Explanatory approach. The sample was taken from 100 santri at Al-Falah Ploso Islamic Boarding School, selected using a systematic random sampling technique. Data collection was carried out using questionnaires and interviews. The results of this study show that the digital divide experienced by santri is a gap in the stage of physical and material access, santri skills in operating gadgets, and the use of the gadgets themselves. Pesantren today also experiences cultural backwardness. This can be seen from the complexity of pesantren responses to the internet and the flow of digitalisation of pesantren that is not going well.